2020
DOI: 10.1186/s13104-020-05205-z
|View full text |Cite
|
Sign up to set email alerts
|

Fermented soy supplementation improves indicators of quality of life: a randomized, placebo-controlled, double-blind trial in adults experiencing heartburn

Abstract: Objective To determine if fermented soy supplementation relieves heartburn and improves gastrointestinal symptoms and quality of life, a randomized, double-blind parallel study was conducted with adults experiencing mild or moderate heartburn. Participants consumed up to 3, 1 g sachets of flavored, Lactobacillus delbrueckii fermented with soy flour (n = 23) or placebo (maltodextrin) (n = 27) sachets per heartburn incident as needed for 3 weeks. Symptom intensity at 5, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…We calculated using the HED convertation method in the previous papers, in which a human supplement dose was converted to rats [ 11 , 12 ]. The clinical dose of Gastro-AD ® ranges from 500 mg to 3000 mg/day [ 10 , 13 ], which for the converted dose of Gastro-AD ® ranges from 51.7 mg to 310 mg/kg/day in rats. After oral administration of 1 mL of rebamipide or Gastro-AD ® for 14 days, 1 mL of rebamipide or Gastro-AD with 1 mL of 40% ethanol was administrated for 7 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated using the HED convertation method in the previous papers, in which a human supplement dose was converted to rats [ 11 , 12 ]. The clinical dose of Gastro-AD ® ranges from 500 mg to 3000 mg/day [ 10 , 13 ], which for the converted dose of Gastro-AD ® ranges from 51.7 mg to 310 mg/kg/day in rats. After oral administration of 1 mL of rebamipide or Gastro-AD ® for 14 days, 1 mL of rebamipide or Gastro-AD with 1 mL of 40% ethanol was administrated for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…Fermentation causes different physical and chemical changes in soybean according to the different organisms and fermentation conditions used [ 9 ]. Fatani et al [ 10 ] showed that soybean fermented using Lactobacillus delbrueckii ssp. delbrueckii Rosell-187 suppressed heartburn occurrence in individuals who experienced mild or moderate heartburn.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, in clinical and preclinical studies, GAD was associated with immunoregulatory activity, with reduced gastric inflammation and acid secretion in mice after an ethanol/HCl challenge, [ 30 ] reduced gastric ulcer scores in equine use, [ 32 ] and showed quality‐of‐life improvements in humans experiencing heartburn. [ 31 ] In a trial involving a GAD‐containing investigational product, the pain‐reduction effects reported in the studies were rapid, with >60% of respondents reporting pain reduction within 30 min. [ 62 ] Given the pain reduction timeline, cyclooxygenase‐2 (COX‐2) inhibition could play a role, reducing inflammation by arresting the conversion of arachidonic acid to prostaglandins, the mechanism through which NSAIDs exhibit efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Trials in adults’ experiencing heartburn demonstrated that quality of life parameters improved within the GAD group versus control, with potential decreases in heartburn scores over time. [ 31 ] Equine trials used GAD with efficacy to manage squamous ulcers. [ 32 ] Early clinical studies in eastern Europe, under the old trade name Gastropharm, demonstrated an antiulcerative effect.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a nutritious and healthy food, which could rapidly neutralize gastric acid, heal ulcers and relieve symptoms, is in urgent need. Gastro-AD soy protein powder is derived from ferments of soy by Lactobacillus delbrueckii subsp., which can significantly alleviate stomach symptoms such as heartburn and stomach pain [5,6]. In vitro studies indicated that dietary fibers (resistant starch) can effectively protect rats from gastric mucosal damage caused by alcohol [7,8].…”
Section: Introductionmentioning
confidence: 99%